Colliding Impulsive Gravitational Waves - Yavuz, Nutku; Mustafa, Halilsoy (Physical Review Letters, American Physical Society (APS), 1977)
We formulate the problem of colliding plane gravitational waves with two polarizations as the harmonic mappings of Riemannian manifolds and construct an exact solution of the vacuum Einstein field equations describing the interaction of colliding impulsive gravitational waves which in the limit of collinear polarization reduces to the solution of Khan and. Penrose.
The file in this item is the publisher version (published version) of the article. His surname was HALIL (i.e. his father’s name) until 1980. Since then, by a surname law of Cyprus Turkish Federated State his surname has been changed into HALILSOY.
Keywords: gravity; gravitational waves; Coliding waves